Integrating Mathematical and Biomechanical Models in Sports Performance: A Multidisciplinary Approach - Bendo , Aida; Maraj , Elda; Kosta, Orkida (South Eastern European Journal of Public Health, 2025)
Background: The integration of mathematical and biomechanical models into sports science has revolutionized the approach to performance analysis, injury prevention, and training optimization across various sports disciplines. These models provide a quantitative framework to understand complex human movements and the interactions between athletes and their environment. The application of these models has become increasingly sophisticated with advancements in technology, offering athletes and coaches valuable insights to enhance athletic performance. Aim of Study: This review article aims to comprehensively synthesize current research on the application of mathematical and biomechanical models in sports, to evaluate the effectiveness of these models and to explore their applications in sports disciplines and rehabilitation regimes. Methods: The review encompasses a systematic search of peer-reviewed literature, including journal articles, conference proceedings, and dissertations, from the past two decades. Key databases such as PubMed, Scopus, and Web of Science were queried using relevant keywords related to mathematical modeling, biomechanics, and sports performance. Studies were included if they applied quantitative models to analyze or predict sports performance, injury risk, or rehabilitation outcomes in any sport. Results: The findings indicate a wide range of applications for mathematical and biomechanical models, from predicting the outcomes of competitive events to optimizing training regimens. Advanced computational techniques, such as finite element analysis and musculoskeletal modeling, have provided detailed insights into the biomechanical demands of sports-specific movements. These models have also been instrumental in developing personalized training interventions and informing equipment design to enhance performance and reduce injury risk. Discussion: The review discusses the versatility of mathematical and biomechanical models in various sports, highlighting their contribution to the understanding of athletic performance. The integration of these models with wearable technology and data analytics has further expanded their potential applications. However, the complexity of human movement and the variability between individuals present challenges in model development and validation. Conclusion: Mathematical and biomechanical models have become indispensable tools in modern sports science, offering objective and detailed analyses for sports analysis and rehabilitation. While the potential benefits are substantial, future research should focus on addressing the current limitations and enhancing the predictive capabilities of these models. Continued innovation in this field promises to further elevate the performance and well-being of athletes across all levels of sport.